Deus Trindade (God as a Trinity). DOI: 10.5752/P.2175-5841.2012v10n26p522 - Burocchi, Aurea Marin (2012)
The Holy Trinity is the novelty of God presented by Jesus Christ. Without contradicting Jewish monotheism, the reflection for a dogmatic formulation lasted for four centuries. Subsequently, the issue of the trinity was forgotten in the Church for 1,600 years. The importance of this issue is currently being rediscovered not only in the liturgy but also in life and ecclesial reflection. The unity in love on the part of the three distinct persons, Father, Son and Holy Spirit, stimulates spirituality and experience of the Christians today. To do so, one needs the assistance of the humanities that allow the update of the dogma of language without losing its essential content. The reflection of the Neapolitan theologian Bruno Forte is of great value to the current theology because it respects the dogmatic formulation and also uses categories and languages appropriate to an understanding of contemporary man. The Trinity of God has something important to say about the man himself because man was created as God’s image. (Gn 2,26).
A novidade do Deus cristão apresentado por Jesus Cristo é a Trindade. Sem contradizer o monoteísmo judeu, a reflexão para formulação dogmática se estendeu por quatro séculos. Sucessivamente, a Trindade foi tema esquecido na Igreja por 1.600 anos. Sua importância está sendo redescoberta não somente na liturgia, mas, também, na vida e na reflexão eclesial. A unidade no amor dos Três distintos, Pai, Filho e Espírito Santo, estimula a espiritualidade e a vivência do cristão de hoje. Para tanto, é necessário o auxílio das ciências humanas, que permitem a atualização da linguagem do dogma sem a perda do seu conteúdo fundamental. A reflexão do teólogo napolitano Bruno Forte dá uma grande contribuição para a teologia atual, respeitando a formulação dogmática e, ao mesmo tempo, buscando categorias e linguagens apropriadas para a compreensão do homem contemporâneo. A Trindade de Deus tem algo importante a dizer para o ser humano de hoje a respeito de si mesmo, pois que feito “à imagem e semelhança de Deus” (Gn 2, 26).
Keywords: Love; Holy Spirit; Son; Father; Trinity; Amor; Filho; Pai; Trindade; Bundesstaat Espírito Santo